OP0161 Dose reduction and/or withdrawal of anti-TNF treatment in psoritic arthritis. (23rd January 2014) - Lόpez-Vives, L.; Estrada, P.V.; Martín-Esteve, I.; Aparicio, M.; Juanola, X.; Nolla, J.M.; Rodríguez-Moreno, J.
Abstract : Background: Psoriathic arthritis (PsA) represents a high sanitary cost, given mainly by disability and disease duration, comparable with rheumatoid arthritis or ankylosing spondylitis. Anti-TNF agents have created a breakthrough in the treatment of PsA. However, TNF blockers are very expensive and are not directly accessible to all patients, depending on either a national health system or private insurance. Objectives: The aim of our study was to analyze the possibility of dose optimization or even its withdrawal once clinical remission or minimal disease activity was attained. Methods: Analysis of a prospective cohort of patients attending a monographic clinic for PsA from 1992 to 2011 was performed at a Rheumatology service of a university hospital. The patient follow-up was executed by the same doctor since the beginning and was evaluated based on a standard protocol. All patients satisfied validated CASPAR criteria for PsA, and were at least visited once during 2010. The database includes demographic data, clinical characteristics, periodical evaluation and treatment regimen. Regarding the anti-TNF treatment, we recorded the following data: reasons for indication (excluding those in whom the prescription was mainly cutaneous), treatment duration, dose reduction, reasons for withdrawal, retreatment and response to its reintroduction. The indication for the biological treatment was performed according to the Spanish Society of Rheumatology's concensus on the use of biological therapies in PsA. Based on a preestablished criteria, the clinician in charge lowered the dose if the patient reached and maintained remission (DAS28<2.6 and normalization of acute fase reactants) for a minimum of six months; or discontinued the anti-TNF if after the progressive dose reduction the patient kept remission for a year. A cut down on the doses was defined as: Infliximab (INF) <3 mg/kg/8week; Etanercept (ETN) <50 mg/week and Adalimumab (ADA) <40 mg/2 weeks. Concomitant use of DMARD was kept in most of the patients. We estimated the real cost of each anti-TNF in every patient and compared it with the expected cost if the standard dose was received. Results: Of the 255 patients (113 women, 112 men) we selected those that had been treated with at least one anti-TNF agent (79 patients, 35%); of these 21 were excluded for mainly having a cutaneous indication and 7 because of missing data. Among the 51 patients (23%) with primarily articular indication, we collected 17 treatments with INF, 33 with ETN and 21 with ADA. Within de patients receiving INF, in two (12%) dose reduction was possible and no treatment withdrawal was attained. Among the patients with ETN, 16 (48%) achieved dose-lowering and in five (15%) dose suspention. Of the 21 with ADA, dose tapering was carried out in 7 (33%) and withdrawal in 5 (24%). Concerning those 10 patients (13%) in whom anti-TNF withdrawal was carried but had to be prescribed once again for outcome motifs, the medium length, given in months of treatment suspension, was 5 for ETN (with an extreme value of 33) and 8 for ADA. Conclusions: In a high percentage of patients, dose reduction for anti-TNF drugs was possible. On the other hand, in a much smaller number of patients, complete withdrawal was unviable because of disease relapse. This treatment regimen would involve a significant cost reduction without changing the patient's quality of life. Disclosure of Interest: None Declared